Explaining differences in the flow-performance sensitivity of retail and institutional mutual funds – International evidence - Miguel, A. (2020)
We use data from 13 countries to study differences in the flow-performance sensitivity between institutional and retail investors. Our results show marked differences between non-US and the US in how institutional and retail investors react to past performance. Compared to retail investors, institutional investors sell more poor performers and buy less top performers outside the US, while there is no difference in how institutional and retail investors react to past performance in the US. When we split our sample into countries with more and less sophisticated investors, our results show significant differences in the flow-performance sensitivity of institutional and retail investors. Overall, our findings are consistent with institutional investors being more sophisticated than retail investors but only in countries where investors are on average less sophisticated.